2011
DOI: 10.3758/s13421-011-0160-6
|View full text |Cite
|
Sign up to set email alerts
|

Readers’ use of source information in text comprehension

Abstract: In two experiments, we examined the role of discrepancy on readers' text processing of and memory for the sources of brief news reports. Each story included two assertions that were attributed to different sources. We manipulated whether the second assertion was either discrepant or consistent with the first assertion. On the basis of the discrepancy-induced source comprehension (D-ISC) assumption, we predicted that discrepant stories would promote deeper processing and better memory for the sources conveying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
128
0
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 154 publications
(160 citation statements)
references
References 56 publications
24
128
0
8
Order By: Relevance
“…Thus, the presence of conflicting opinions contributed to the effects of source information to a certain extent, but did not eliminate the effects. This is not only consistent with the discrepancy-induced source comprehension hypothesis (Braasch et al, 2012), but also extends the theory. For example, the effects of intra-text comprehension were found in only the expert-expert source condition when both texts presented negative opinions toward GM foods.…”
Section: Discussiwnsupporting
confidence: 78%
See 2 more Smart Citations
“…Thus, the presence of conflicting opinions contributed to the effects of source information to a certain extent, but did not eliminate the effects. This is not only consistent with the discrepancy-induced source comprehension hypothesis (Braasch et al, 2012), but also extends the theory. For example, the effects of intra-text comprehension were found in only the expert-expert source condition when both texts presented negative opinions toward GM foods.…”
Section: Discussiwnsupporting
confidence: 78%
“…When participants notice conflicting information in texts, they would pay more attention to source information and be likely to evaluate it. Braasch, Rouet, Vibert, and Britt (2012) confirmed this hypothesis by eye movement recording experiments. They showed that participants gazed longer at inconsistent information compared to consistent information when they read text.…”
Section: Experiments 2: Coordinative Viewssupporting
confidence: 76%
See 1 more Smart Citation
“…Braasch et al (2012) presented brief fictitious news articles on various topics containing two sources (embedded characters) that made specific assertions about the situation depicted in the text. Consider the following example, in which two claims regarding the cause of a fire in a building are reported: BThe detective claims that the fire in the warehouse was caused by a malfunction in the electrical circuit.…”
Section: Discrepancies Sourcing and The Documents Model Frameworkmentioning
confidence: 99%
“…Previous research has found evidence that discrepancies prompt readers to include source-to-content links in their representation of the text (Braasch, Rouet, Vibert, & Britt, 2012;Rouet, Le Bigot, de Pereyra, & Britt, 2016). This study examines the hypothesis that discrepancies also prompt readers to strengthen the association between the sources issuing the conflicting statements.…”
mentioning
confidence: 93%